Icotinib derivatives as tyrosine kinase inhibitors with anti-esophageal squamous carcinoma activity - Chen, Xiaojie; Mao, Long-Fei; Tian, Siqi; Tian, Xueli; Meng, Xueqiong; Wang, Mu-Kuo; Xu, Weifeng; Li, Yue-Ming; Liu, Kangdong; Dong, Zigang (Frontiers in Pharmacology, 2022)
Previous report showed that a variety of icotinib derivatives bearing different 1,2,3-triazole moieties, which could be readily prepared via copper (I)-catalyzed cycloaddition (CuAAC) reaction between icotinib and different azides, exhibited interesting activity against different lung cancer cell lines such as H460, H1975, H1299, A549 or PC-9. To further expand the application scope of the compounds and to validate the function of triazole groups in drug design, the anti-cancer activity of these compounds against esophageal squamous carcinoma (ESCC) cells was tested herein. Preliminary MTT experiments suggested that these compounds were active against different ESCC cell lines such as KYSE70, KYSE410, or KYSE450 as well as their drug-resistant ones. Especially, compound 3l showed interesting anticancer activity against these cell lines. The mode of action was studied via molecular docking, SPR experiments and other biochemical studies, and 3l exhibited higher binding potential to wild-type EGFR than icotinib did. In vivo anticancer study showed that 3l could inhibit tumor growth of cell-line-derived xenografts in ESCC. Study also suggested that 3l was a potent inhibitor for EGFR-TK pathway. Combining these results, 3l represents a promising lead compound for the design of anti-cancer drugs against ESCC.